Electrophysiology versus clinical outcomes of tethered cord surgery assisted with intraoperative mep and ssep in Hospital Queen Elizabeth Kota Kinabalu Sabah : a prosperctive cohort pilot study - Francis, Jacintha Vikeneswary (2015)
Introduction: The tethered cord syndrome (TCS) is an uncommon disease caused by an abnormal stretching of the spinal cord, reported incidence of 0.05 to 0.25 per births untethering of the tight filum terminale. Spinal dysraphism is associated with tethered cord, which includes malformations like myelomeningocele, lipomyelomeningocele, tight filum terminale, split cord malformation, and dermoid sinus. Once the symptoms have developed, the patient has a terthered cord syndrome (TCS). These symptoms may either be neurological, urological, orthopedic, or pain. The goal of surgery is to detether the cord by disconnecting its aberrant tightening attachments, and to relieve the cord from continuous stretching forces. Tethering structures may consist lipoma, fibrous bands, non-functional nervous tissue, or a dermoid sinus tract. Peroperatively it can be difficult to distinguish between functional neural tissue and these non-functional tethering structures. Permanent neurological complications were reported in about 4.5% of patients, and this was high as 10.9% when transient complications were taken into account. Intraoperative neurophysiological monitoring (IONM) may help to protect the functional nervous tissue and prevent postoperative neurological deficits. There is no evident consensus on the exact methods of multimodal (M) IONM that should be used during surgery for TCS. The use of intraoperative neurophysiological monitoring (IONM) may contribute to the safety in tethered cord surgery. We present a series of 15 patients with a wide variety of morphology of spinal dysraphism. All patients were operated for reasons of a tethered cord with the preoperative use of IONM. The usage of IONM in the different age groups and its potential contribution to the safety of the procedure are investigated. This will further aid in prognosticating the neurological outcome of patients undergoing TC surgery. This study also helps us in evaluating the importance of IONM in tethered cord surgery. Conclusion: NIOM during TCS surgery can be used not only to aid with safety of surgery but in prognosticating on the postoperative outcome of the patient. This will eventually help in reducing operative morbidity , thus giving a likely favourable outcome.